Incubation routine and associated changes in body mass of Gould's Petrel (Pterodroma leucoptera). (3rd April 2018) - Kim, Yuna; Priddel, David; Carlile, Nicholas
ABSTRACT: Procellariiformes have prolonged incubation shifts, with breeding birds enduring long periods of fasting and substantial reductions in body mass. These changes can be physically demanding and parents must balance their own energy requirements with the needs of their unhatched young. The incubation routine and associated changes in body mass of breeding Gould's Petrel ( Pterodroma leucoptera ) were studied to explore the relationships between body mass, incubation shift duration and nest desertion. The incubation routine of Gould's Petrel was similar to other Procellariiformes, although shift length was particularly long for a bird of this size. Failure to complete incubation was due to egg damage or nest desertion. Temporary egg abandonment was observed in successful as well as in failed breeders, although eggs abandoned for longer than 1 day all failed. Nest desertions generally occurred before the normal duration of the incubation shift rather than after excessively long shifts caused by the late return of the partner. We conclude that incubation success was limited by both the condition of birds at the start of the shift and their tenacity to remain until relieved by their partner.